Rare protein‐coding variants implicate genes involved in risk of suicide death. Issue 8 (27th May 2021) - DiBlasi, Emily; Shabalin, Andrey A.; Monson, Eric T.; Keeshin, Brooks R.; Bakian, Amanda V.; Kirby, Anne V.; Ferris, Elliott; Chen, Danli; William, Nancy; Gaj, Eoin; Klein, Michael; Jerominski, Leslie; et al.
Abstract : Identification of genetic factors leading to increased risk of suicide death is critical to combat rising suicide rates, however, only a fraction of the genetic variation influencing risk has been accounted for. To address this limitation, we conducted the first comprehensive analysis of rare genetic variation in suicide death leveraging the largest suicide death biobank, the Utah Suicide Genetic Risk Study (USGRS). We conducted a single‐variant association analysis of rare (minor allele frequency <1%) putatively functional single‐nucleotide polymorphisms (SNPs) present on the Illumina PsychArray genotyping array in 2, 672 USGRS suicide deaths of non‐Finnish European (NFE) ancestry and 51, 583 NFE controls from the Genome Aggregation Database. Secondary analyses used an independent control sample of 21, 324 NFE controls from the Psychiatric Genomics Consortium. Five novel, high‐impact, rare SNPs were identified with significant associations with suicide death ( SNAPC1, rs75418419 ; TNKS1BP1, rs143883793 ; ADGRF5, rs149197213 ; PER1, rs145053802; and ESS2, rs62223875). 119 suicide decedents carried these high‐impact SNPs. Both PER1 and SNAPC1 have other supporting gene‐level evidence of suicide risk, and psychiatric associations exist for PER1 (bipolar disorder, schizophrenia), and for TNKS1BP1 and ESS2 (schizophrenia). Three of the genes ( PER1, TNKS1BP1, and ADGRF5 ), together with additional genes implicated by genome‐wide association studies on suicidal behavior, showed significant enrichment in immune system, homeostatic and signal transduction processes. No specific diagnostic phenotypes were associated with the subset of suicide deaths with the identified rare variants. These findings suggest an important role for rare variants in suicide risk and implicate genes and gene pathways for targeted replication.